Factores comerciales de la microempresa Víctor´S Flower y preferencias del consumidor de flores del cantón Latacunga. - Alcarraz Santafé, Jessica Margoth (2020)
This research project aimed to identify the commercial factors that determine the preferences of the flower consumer in the Latacunga Canton, considering that at present the microenterprise Victor's Flower should take into account the consumer behavior, since they are based on the tastes, preferences and needs that customers have towards a certain product, which can allow the microenterprise to establish strategies to achieve a position in the consumer's mind. In order to identify the commercial factors that determine the preferences of the flower consumer of the Victor’s Flower microenterprise, the theoretical bases of the variables involved in the study were investigated, techniques and instruments were used as an important part for the development of the research. The sources of information used were primary and secondary, as well as descriptive research which allowed to describe the problem involved in the project. Based on the results obtained through the analysis of the surveys, it was possible to determine which are the most relevant factors that the population considers when deciding to purchase, the data obtained was made the matrix of the consumer profile to determine the preferences of the customers who purchase the flowers; then a comparative table was made in relation to commercial factors and it was concluded that customers are looking for options, analyzing the alternatives and characteristics of the product to make the best decision, on the other hand, it was concluded that Victor's Flower lacks factors that are important for customers, which is why strategic guidelines were defined that in one way or another will allow the microenterprise to improve its sales level